Unlocking the sustainable production indicators: Novel TESCO based fuzzy AHP approach - Muhammad Hashim; Muhammad Nazam; Muhammad Abrar; Zahid Hussain; Muhammad Nazim; Rizwan Shabbir (Cogent Business & Management, 2021)
Sustainable production is becoming an important slant through which business enterprises prepare for achieving sustainable development goals. The concept of sustainable manufacturing deals with the development of various items that may utilize minimum resources and are safer for the society at a reasonable price. The present research problem explores and evaluates the production indicators pertaining to the achievement of sustainability in a textile supply chain. In this research, five main indicators and twenty five sub-indicators were determined through extensive review of literature and experts confirmation. This study proposes a novel TESCO-based fuzzy AHP approach for the evaluation of sustainability dimensions of textile sector under uncertain environment. This paper investigates the key sustainable dimensions based on technical (T), ecological (E), socio-economic (S), core competencies (C) and operational (O) considerations to prioritize the sustainable production indicators (SPIs). The fuzzy analytical hierarchy process (FAHP) approach has been applied to compute the weight vectors of dimension impacting the (SPIs). The findings depict that technical indicators have significant impact whereas operational indicators have the least impact in the decision-making process of a textile sector. Furthermore, a sensitivity analysis is applied to check the robustness among the criterion ranking and suggest possible measures to improve operational business excellence. Finally, the paper brings out a more systematic decision support toolkit and implications for the concerned stakeholders to formulate the policies regarding physical production and distribution of products.
Keywords: 650; sustainable production indicators; fuzzy AHP; sensitivity analysis; textile sector